2012
DOI: 10.1088/0741-3335/54/8/085001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of finite radial transport on the structure and evolution ofm/n= 2/1 neoclassical tearing modes on MAST

Abstract: Finite radial transport around magnetic islands is believed to play an important role in the threshold, spatial structure and temporal evolution of neoclassical tearing modes (NTMs). We report on novel measurements of NTMs with mode structure m/n = 2/1 on the MAST spherical tokamak (ST), which have allowed a direct evaluation of the effect of transport on island behaviour for the first time on an ST. Temperature profiles obtained with the upgraded Thomson scattering (TS) system on MAST have been used to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Experimentally observed T e structures of magnetic islands are well described [11][12][13][14] by a simple anisotropic diffusion model 15 (χ ⊥ ∇ 2 ⊥ T e + χ ∇ 2 T e = 0, where χ is the parallel electron thermal diffusivity), where T e is flat if χ ⊥ = 0 at the O-point, but finite χ ⊥ results in a boundary layer L χ ∝ χ 1/4 ⊥ which decreases the δj BS drive of the NTM. Inside the island, χ ⊥ is reduced to neoclassical level [12][13][14] , in accord with local reduction of ion temperature gradient (ITG) and trapped electron mode (TEM) scale turbulence [16][17][18] . Under these conditions L χ ≈ 1.2 cm 14 , but in principle L χ ≈ 4 cm is possible by restoring n inside the island.…”
Section: Introductionmentioning
confidence: 94%
“…Experimentally observed T e structures of magnetic islands are well described [11][12][13][14] by a simple anisotropic diffusion model 15 (χ ⊥ ∇ 2 ⊥ T e + χ ∇ 2 T e = 0, where χ is the parallel electron thermal diffusivity), where T e is flat if χ ⊥ = 0 at the O-point, but finite χ ⊥ results in a boundary layer L χ ∝ χ 1/4 ⊥ which decreases the δj BS drive of the NTM. Inside the island, χ ⊥ is reduced to neoclassical level [12][13][14] , in accord with local reduction of ion temperature gradient (ITG) and trapped electron mode (TEM) scale turbulence [16][17][18] . Under these conditions L χ ≈ 1.2 cm 14 , but in principle L χ ≈ 4 cm is possible by restoring n inside the island.…”
Section: Introductionmentioning
confidence: 94%
“…1 (d)] are consistent with an island centered at R s . The full width of the island is about W = 15 cm (defined as the maximum radial distance between the island separatrices), determined by fitting the numerical solutions of the heat transport model of magnetic islands to T e data by χ 2 minimization [13,14]. The toroidal Mirnov-coil array data shows a dominant n = 1 toroidal harmonic component of magnetic field fluctuations ( B) at the tokamak wall which is also consistent with a 2/1 island.…”
mentioning
confidence: 99%
“…Careful experiments on JET have shown that the agreement between the data and experiment is much better when the threshold effects are taken into account 20 , and this can be seen in Fig 5, where the predicted evolution is plotted (1) neglecting threshold effects, (2) including only the transport effect and (3) including only the polarisation effect. Recent high resolution temperature profile measurements in the vicinity of NTMs on MAST indicate that the transport effects are likely to play a role in the threshold physics 21 .…”
Section: Experimental Evidencementioning
confidence: 99%
“…Experiments have probed the conditions for NTM onset rather deeply 21,25,26 . In particular, roles have been deduced for both collisionality and  * (which is the ratio of ion Larmor radius to minor radius).…”
Section: Experimental Evidencementioning
confidence: 99%